U.S. food policy to address diet-related chronic disease - Matthews, Emily D.; Kurnat-Thoma, Emma L. (Frontiers in Public Health, 2024)
Poor diet is the leading cause of mortality in the U.S. due to the direct relationship with diet-related chronic diseases, disproportionally affects underserved communities, and exacerbates health disparities. Evidence-based policy solutions are greatly needed to foster an equitable and climate-smart food system that improves health, nutrition and reduces chronic disease healthcare costs. To directly address epidemic levels of U.S. diet-related chronic diseases and nutritional health disparities, we conducted a policy analysis, prioritized policy options and implementation strategies, and issued final recommendations for bipartisan consideration in the 2023–24 Farm Bill Reauthorization. Actional recommendations include: sugar-sweetened beverage taxation, Supplemental Nutrition Assistance Program (SNAP) fruit and vegetable subsidy expansion, replacement of ultra-processed foods (UPF) with sustainable, diverse, climate-smart agriculture and food purchasing options, and implementing “food is medicine.”